Pengaruh Komunikasi Digital Terhadap Pola Komunikasi Pada Nilai-Nilai Budaya Masyarakat Modern - Herman, Herman (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
The development of digital technology has brought significant changes in various aspects of life, including communication patterns in modern society. This study aims to analyze the influence of digital communication on communication patterns on the cultural values of modern society. Digital communication, which is characterized by the use of social media, instant messaging applications, and other digital platforms, influences the way people interact and convey inherited cultural values. These changes raise questions about how cultural values, such as mutual cooperation, politeness, and respect for tradition, are maintained or shifted in the digital era. Through a qualitative approach, it was found that digital communication tends to facilitate efficiency in social interaction, but on the other hand, there is the potential for a shift or decline in the quality of the delivery of cultural values. Some cultural values have adapted to suit the dynamics of digital communication, while others have begun to fade due to the influence of a more easily accessible global culture. This research concludes that although digital communication offers opportunities to expand the spread of cultural values, there are challenges in maintaining the essence and integrity.